Civic resilience during conflict: Syria's local councils. (1st November 2018) - Saleh, Layla
With the 'return of the state' in Syria, Assad's 'resilience' is a puzzle increasingly broached in both media and academic discourses. This article seeks to turn such an approach on its head, examining the resilience not of the state, but of bottom-up Syrian popular mobilization and organization. Persistent if changing Syrian civic modes and practices are thus mediated by conflict, but also part and parcel of ongoing resistance against the authoritarian state. A survey of Syrians' 'revolutionary' media landscape reveals a set of shifting emphases. Appeals soliciting global support for an uprising seeking freedom and dignity give way to lamentations over disappointed yet tenacious Syrian aspirations. The article then explores Syrian 'democratic learning' through a mini-case study of opposition-controlled local councils. Drawing on original interview data, it argues that these councils exhibit 'civic resilience' as they navigate and adopt international norms discourses to protest and resist not just Assad but also international actors, and gradually take up democratic processes including elections. Despite uncertainty with respect to its institutional dividends in Syria, 'democratic learning' is a promising, understudied area for further exploration in the bloody politics of the country's uprising.